Ultrasound-assisted polymerization of P(AM-DMDAAC): Synthesis, characterization and sludge dewatering performance. Issue 6 (December 2017) - Liao, Yong; Zheng, Xinyu; Zhang, Zhaoqing; Xu, Bincheng; Sun, Yongjun; Liu, Yongzhi; Zheng, Huaili
Abstract: P(AM-DMDAAC) (PDA) was synthesized by ultrasound assisted polymerization with dimethyl diallyl ammonium chloride (DMDAAC) and acrylamide (AM) as the monomers. The reaction conditions of polymerization were investigated by single factor approach and L16 (4 5 ) orthogonal array. Results showed that the intrinsic viscosity of PDA could reach 14.6 dL/g with the optimum polymerization conditions as following: monomer concentration of 30%, temperature of 30 °C, ultrasound time of 1 h, monomer mass ratio (m(DMDAAC) :m(AM) ) of 2:8, initiator concentration of 0.4‰, sodium benzoate concentration of 0.5‰, ethylene diamine tetraacetic acid (EDTA) concentration of 0.5‰, solution pH value of 6 and urea concentration of 0.3‰. The self-made PDA was characterized by several instruments. The results of FTIR and 1 HNMR indicated that PDA was successfully polymerized by AM and DMDAAC. DTA-TGA showed that PDA was very stable at room temperature. And SEM proved the porous and mushroom shaped structure of PDA. For PDA used as flocculant in sludge dewatering experiment, the results showed that the filter cake moisture content and the supernatant turbidity could be reduced to 66.3% and 24.1 NTU, respectively. Comparing with other four cationic polyacrylamides, the filter cake moisture content could be reduced by 2.0-7.4% and the supernatant turbidity could be reduced by 18.3-32.1% via using self-made PDA, that was to say, the dewatering efficiency of self-made PDA was the best. Besides, the optimal dosage of self-made PDA was the least, and the cost analysis showed that it was also favorable, a 14.6-39.3% cost could be saved by using self-made PDA.